Foot and Mouth Disease: An Exotic Animal Disease that must be Alert of Entry into Indonesia - R.M. Abdul Adjid (Indonesian Center for Animal Research and Development, 2020)
Foot and Mouth Disease (FMD) is a highly contagious disease that attacks cloven hoofed animals. Among the animals primarly livestock that sensitive to FMD include cattle, bufalloes, pigs, sheep, and goats. The causative agent of FMD is the Foot and Mouth Disease Virus (FMDV). This disease is greatly feared by all countries because it may cause great loss of economic impact. There are still many countries in the world that are not yet free from FMD. The World Animal Health Organization (OIE/ Office des Internationale Epizootis) has included this disease in the list of disease that must be reported as “notifiable disease”. This FMD has become exotic for Indonesia since 1990, and currently it is included in the list of strategic infectious animal diseases in Indonesia. With current situation where the traffic of people and goods between countries in the world is very fast and frequent, it is possible for the disease to enter Indonesian territory. This paper discusses the FMD with aim of increasing alertness and readiness in preventing the entry and spread of the disease to Indonesia.